COMMENTS ON "AN EMPIRICAL DERIVATION OF HIERARCHIES OF PROPOSITIONS RELATED TO TEN OF PIAGET'S SIXTEEN BINARY OPERATIONS". - Bady, Richard (Journal of Research in Science Teaching, 1977)
The article presents views and insights of the author on the study regarding the empirical deviation of hierarchies of propositions related to ten of Piaget's binary operations. The researchers have found out that of the 16 binary operations, the ones with three positive instances are more difficult than the ones with two positive instances. They also assumed that possession of each of the ten binary operations investigated is confirmed by accurate use of the corresponding propositional operations. Logical analysis of the requirements of the task is called for in interpreting any such data.